Poetic Vision and (In)visible Pain in Antonio Méndez Rubio’s Trasluz - Paul Cahill (Studies in 20th & 21st Century Literature, 2012)
Since the 1980s, visibility has played a key role in debates surrounding Spanish poetry. Novísimo ‘very new’ poets have highlighted and explored the instability and uncertainty of the gaze, while poetas de la experiencia ‘poets of experience’ have more readily accepted the visible without questioning it or the mechanisms used to construct it. Poets who entered the literary scene in the mid to late 1990s have also entered this discussion. Antonio Méndez Rubio, the author of twelve poetry collections and numerous critical and theoretical works, is a poet whose work does not fit easily within the categories usually employed to discuss contemporary Spanish poetic production dealing with social reality. Nevertheless, his poetry still seeks to engage the reader and help the reader engage critically with his or her material and discursive surroundings. This essay will show that the problematization of the gaze and the (in)visible in Trasluz ‘Throughlight’ by Méndez Rubio explores the inherently political nature of what is seen, how we see it, and how we (re)present it in poetry. His stance vis-à-vis these issues indicates a marked departure from the dominant poetic trends that characterized Spanish poetry of the 1980s and 1990s, thereby providing a glimpse into both the present and future of Spanish poetry.
Keywords: poetry; poetic vision; invisibility; visibility; novísimo; poetas de la experiencia; poets of experience; Antonio Méndez Rubio; social reality